Delayed fracture in cold blanking of ultra-high strength steel sheets. Issue 1 (2019) - Mori, Ken-ichiro; Abe, Yohei; Sedoguchi, Kyohei
Abstract: Hydrogen-induced delayed fracture at cold-blanked edges of 1–1.5 GPa ultra-high strength steel sheets was investigated. The blanked edges undergo large shear deformation and tensile residual stress, and thus the risk of delayed fracture is high, especially for the 1.5 GPa sheet. The effects of residual stress, surface quality and hardness of the sheared edge on the occurrence of delayed cracking were examined. Delayed cracking was caused by press blanking, whereas no cracking occurred for laser blanking because of compressive residual stress. For the 1.5 GPa sheet, delayed cracking was prevented by heating above 250 °C and a stain above 0.005.